1995
DOI: 10.1136/vr.136.7.169
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the incidence of Salmonella species and Enterobacteriaceae in poultry feeds and feed components

Abstract: Between July 1990 and April 1991 the rate of contamination with Salmonella species of poultry feeds and feed components used by the Dutch feed industry was surveyed. Ten per cent of 360, 10 g samples of poultry feeds were found to be contaminated. Mash feeds, mostly used for layer-breeders, were far more frequently (21 per cent) contaminated than pelleted feeds (1.4 per cent). The rate of contamination of 130 samples of fish meal was 31 per cent, of 83 samples of meat and bone meal 4 per cent, 58 samples of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 0 publications
1
95
1
5
Order By: Relevance
“…The incidence of Salmonella in poultry feed and feed ingredients were found to be 9.6 % in this study. The incidence of Salmonella in poultry feed and feed ingredients are known to be highly variable ranging from 0 to 78 % [25,26]. Various factors including source and quality of feed ingredients, storage conditions could contribute to this variation.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of Salmonella in poultry feed and feed ingredients were found to be 9.6 % in this study. The incidence of Salmonella in poultry feed and feed ingredients are known to be highly variable ranging from 0 to 78 % [25,26]. Various factors including source and quality of feed ingredients, storage conditions could contribute to this variation.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Salmonella in poultry feed samples was 2.33% and are comparable to levels of 2% in Egypt and 4.4% in Brazil [17,18]. Six isolates of Salmonella from 37 (16.2%) imported broiler fish meal were recovered [19] and mash feed contains fish and meat and bone meals mostly used for layer breeder were far more frequent 21% and 4% respectively [20] contaminated with Salmonella. Broiler and layer feed is one of the important sources of chicken farm contaminated with Salmonella [21].…”
Section: Presence or Absence Enumeration And Percentage Of Salmonellmentioning
confidence: 99%
“…The Salmonella isolation rate in this surveillance was not as high as that reported by Cox et al [2], Veldman et al [16] and Davies and Wray [3]. Davies and Wray [3] reported that S. Enteritidis was isolated on one occasion from an intake pit spillage but not from any bagger ones in a feed mill which 26 serovars of Salmonella were frequently isolated.…”
mentioning
confidence: 50%
“…Davies and Wray [3] reported that S. Enteritidis was isolated on one occasion from an intake pit spillage but not from any bagger ones in a feed mill which 26 serovars of Salmonella were frequently isolated. Whilst Cox et al [2] or Veldman et al [16] did not S. Enteritidis from any feeds. The Salmonella isolation rate from feed samples seems to relate to that from eggs in this area (unpublished data).…”
mentioning
confidence: 99%